INTEGRATION OF TECHNOLOGY IN TEACHING & LEARNING - Hasnah Mohamed, 1966-, editor 535272; Juhazren Junaidi, 1981-, 315363; Hasnah Mohamed, 1966-, contributor 535272; Juhazren Junaidi, 1981-, 315363; Jamalludin Harun, 1971-, contributor 482285; Mohd. Nihra Haruzuan Mohd. Said, 1978-, contributor 601518; Mohd. Syahir Abdul Ghani, contributor 647318; Norah Md. Noor, contributor 523990; Norazrena Abu Samah, contributor 561977; Zaleha Abdullah, contributor 388992; Mohamed Noor Hassan, contributor 647319; Nurazean Maarop, contributor 196873; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2016)
Includes bibliographical references and index.